Gold(I)-catalyzed hydroxy group assisted C(sp(2))-H alkylation of enaminones with diazo compounds to access 3-alkyl chromones - Bagle, Pradip N.; Mane, Manoj V.; Sancheti, Shashank P.; Gade, Amol B.; Shaikh, Samir R.; Baik, Mu-Hyun; Patil, Nitin T. (Organic Letters, 2019)
A strategy for expedient synthesis of 3-substituted chromones from easily available o-hydroxyarylenaminones and diazo compounds has been developed. Carefully conducted experimental and computational studies led us to propose an uncommon mechanistic pathway involving the hydroxyl group assisted alkylation of enaminones with in situ generated gold carbenes.